2020
DOI: 10.1186/s13662-020-02967-5
|View full text |Cite
|
Sign up to set email alerts
|

Hermite–Hadamard-type inequalities via n-polynomial exponential-type convexity and their applications

Abstract: In this paper, we give and study the concept of n-polynomial $(s,m)$ ( s , m ) -exponential-type convex functions and some of their algebraic properties. We prove new generalization of Hermite–Hadamard-type inequality for the n-polynomial $(s,m)$ ( s , m ) -exponential-type convex function ψ. We also o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Awan et al [11] keeping his work on generalizations, introduced a new class called n-polynomial harmonically convex function. Motivated and inspired by the ongoing activities and research in the convex analysis field, we found out that there exists a special class of function known as exponential convex function, and nowadays, a lot of people working are in this field [12,13]. Dragomir [14] introduced the class of exponential type convexity.…”
Section: Introductionmentioning
confidence: 99%
“…Awan et al [11] keeping his work on generalizations, introduced a new class called n-polynomial harmonically convex function. Motivated and inspired by the ongoing activities and research in the convex analysis field, we found out that there exists a special class of function known as exponential convex function, and nowadays, a lot of people working are in this field [12,13]. Dragomir [14] introduced the class of exponential type convexity.…”
Section: Introductionmentioning
confidence: 99%
“…Inequalities have an intriguing mathematical model because of its significant applications in traditional calculus, fractional calculus, quantum calculus, interval calculus, stochastic, time scale calculus, fractal sets, etc. For the applications, we encourage the readers to go through [5,6,7,8]. In such a manner, Ostrowski type inequality is quite possibly one of the most prominent contemplated results.…”
Section: Introductionmentioning
confidence: 99%
“…It is also known as classical equation of (H–H) inequality. The Hermite–Hadamard inequality asserts that, if a function is convex in I for and , then Interested readers can refer to [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] .…”
Section: Introductionmentioning
confidence: 99%
“…Eventually the theory of inequalities may be regarded as an independent area of mathematics. For the applications of inequalities interested readers refer to [1,2,3,4,5,6]. In recent years, a wide class of integral inequalities is being derived via different concepts of convexity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation